2004
DOI: 10.1016/j.str.2004.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Properties of the Human Notch-1 Ligand Binding Region

Abstract: We present NMR structural and dynamics analysis of the putative ligand binding region of human Notch-1, comprising EGF-like domains 11-13. Functional integrity of an unglycosylated, recombinant fragment was confirmed by calcium-dependent binding of tetrameric complexes to ligand-expressing cells. EGF modules 11 and 12 adopt a well-defined, rod-like orientation rigidified by calcium. The interdomain tilt is similar to that found in previously studied calcium binding EGF pairs, but the angle of twist is signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 56 publications
4
118
0
Order By: Relevance
“…S11). By contrast, another NMR study (41), performed on hN1 [11][12][13] at physiologically relevant Ca 2+ concentrations, demonstrated that EGF12 residues are characterized by order parameters >0.8, suggesting that this domain does not contain backbone segments that are dynamic on a fast timescale (42,43). Our crystal structures, obtained in the presence of Ca 2+ , demonstrate that the addition of sugars to T466 does not appear to induce a conformational change either in the orientation of the Thr side chain or more globally in the overall structure of the EGF12 domain, or alter the packing interactions it makes with adjacent cbEGF domains.…”
Section: Discussionmentioning
confidence: 90%
“…S11). By contrast, another NMR study (41), performed on hN1 [11][12][13] at physiologically relevant Ca 2+ concentrations, demonstrated that EGF12 residues are characterized by order parameters >0.8, suggesting that this domain does not contain backbone segments that are dynamic on a fast timescale (42,43). Our crystal structures, obtained in the presence of Ca 2+ , demonstrate that the addition of sugars to T466 does not appear to induce a conformational change either in the orientation of the Thr side chain or more globally in the overall structure of the EGF12 domain, or alter the packing interactions it makes with adjacent cbEGF domains.…”
Section: Discussionmentioning
confidence: 90%
“…EGF 28 is in the Abruptex region of Notch, named for a series of mutations in Drosophila Notch that result in a hyperactive Notch refractory to Fringe (17,62). Recent structural studies have suggested that the presence of calcium-binding motifs reduces the flexibility of the linker between adjacent EGF repeats (63). Most of the EGF repeats in Notch1 contain the calcium-binding motif, and as a result, the linkers are predicted to be rigid (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion experiments have confirmed that EGF 11 and 12 constitute the Notch ligand binding domain [28]. While Notch1 EGF repeats 11-13 made in E.coli, and therefore not O-fucosylated, bind to Delta-expressing cells, this was only observed after tetramerization of the Notch fragment [29]. In fact, elimination of O-fucose from EGF 12 has profound conequences for Notch signaling.…”
Section: Elimination or Acquisition Of O-fucose Sites In Notchmentioning
confidence: 97%